2001
DOI: 10.1348/014466601164768
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reasons given for ineligibility on perceived gender discrimination and feelings of injustice

Abstract: We examine whether the reason given for a negative outcome influences the likelihood of making gender discrimination attributions. Men and women were given one of four reasons for their ineligibility to attend an event: an explicit gender reason, a reason based on an attribute correlated with gender, that same gender-related reason with explanatory information attached, or they were given no reason. Providing participants with a reason based on a gender-related attribute deflected them from making attributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Providing an uninformative, placebic explanation for a small request (''I have to make copies'') produced as much compliance as providing an informative, legitimate explanation (''I'm in a rush''). Kappen and Branscombe (2001) found that participants were more willing to accept being ineligible to attend an event and were less angry about it when an explanation was given, even though that explanation was weak. Similarly, we propose that having any explanation for power differences, even a relatively illegitimate one, may be sufficient for people to accept these differences.…”
Section: Effects Of Power Explanations On the Powerful And The Powerlessmentioning
confidence: 94%
See 1 more Smart Citation
“…Providing an uninformative, placebic explanation for a small request (''I have to make copies'') produced as much compliance as providing an informative, legitimate explanation (''I'm in a rush''). Kappen and Branscombe (2001) found that participants were more willing to accept being ineligible to attend an event and were less angry about it when an explanation was given, even though that explanation was weak. Similarly, we propose that having any explanation for power differences, even a relatively illegitimate one, may be sufficient for people to accept these differences.…”
Section: Effects Of Power Explanations On the Powerful And The Powerlessmentioning
confidence: 94%
“…However, we propose that sometimes the sheer presence of an explanation is enough for people to accept power differences. Past research has shown that people tend to accept even weak or placebic explanations for negative outcomes (e.g., Haines & Jost, 2000;Kappen & Branscombe, 2001;Langer, Blank, & Chanowitz, 1978;Slugoski, 1995). In one of Langer and colleagues' classic studies, a person about to use a copying machine was asked to let someone else use it first.…”
Section: Effects Of Power Explanations On the Powerful And The Powerlessmentioning
confidence: 99%
“…Even placebic explanations led members of a disadvantaged group to feel better and to ascribe favorable characteristics to members of an outgroup that had power over them (see also Kappen & Branscombe, 2001). A memory bias indicated that people were more likely than would be expected by chance to falsely recall that neutral and illegitimate explanations for the power differences were in fact legitimate.…”
Section: Rationalization Of the Status Quomentioning
confidence: 99%
“…Research and theory indicates that permeability and legitimacy of group boundaries, intra versus intergroup social comparison, attributions, and identification with subgroup determine low status group member's reactions to denial of entry into high status groups (Ellemers, Baretto, & Spears, 1999;Tajfel, 1981;Mummendey, Kessler, Klink, Mielke, & Wenzel, 1999;Taylor & McKirnan, 1984). A minimal degree of permeability, perception of self as being close to the criteria of entry, system justification beliefs, seemingly acceptable reasons for exclusion, and blame attributions to in-group are associated with attempts at individual social mobility rather than group oriented attempts at social change (Hine & Montiel, 1999;Kappen & Branscombe, 2001;Sidanius & Pratto, 1999;Wright, Taylor, & Moghaddam, 1990).…”
Section: Characteristics Of the Intergroup Situationmentioning
confidence: 99%
“…The boundaries of the superordinate group, the EU, seem to be fairly but not completely impermeable. Research has shown that even a very low probability of acceptance into the high status group and the flimsiest explanation for rejection are sufficient for legitimization of exclusion and continuation of attempts at social mobility (Kappen & Branscombe, 2001;Wright et al, 1990). Thus, Turkey may continue her attempts at social mobility.…”
Section: Characteristics Of the Intergroup Situationmentioning
confidence: 99%